جهود جمعية العلماء المسلمين الجزائريين في إرسال البعثات الطلابية إلى الخارج - بن بوزريان, عبد الرحمن (جامعة الوادي - University of Eloued, 2018)
لقد أسست مدينة فاس بالمغرب الأقصى لثقافة المقاومة منذ أن احتضنت توقيع معاهدة الحماية على المغرب في 30 مارس 1912، وتعد هذه المدينة من المدن الرئيسية في استقطاب الجزائريين قبل وبعد الاحتلال الفرنسي للجزائر لما تتمتع به من موقع جغرافي ودور حضاري وثقافي باعتبارها العاصمة العلمية للبلاد، فقط كانت محط رحال الكثير من المهاجرين الجزائريين من مختلف المدن الجزائرية لا سيما الغربية منها كتلمسان، ومعسكر، ومستغانم، ووهران، وندرومة..، وقد لعبت دورا حساسا في تعليم وتكوين النخب الوطنية الجزائرية التي انغمرت في صراع مرير في مواجهة المحتل منذ سنة 1830 وإلى غاية 1962، سنوات لم تهدأ فيها قوات الاحتلال الفرنسي عن إذلال الشعب الجزائري. بعدما اتسعت حركة التعليم العربي الحر بالجزائر مع أواخر ثلاثينيات القرن الماضي، وأصبح لديها طلاب مؤهلون لاستئناف دراستهم الثانوية والجامعية، قررت جمعية العلماء المسلمين الجزائريين توجيه بعثات طلابية إلى فاس بالمغرب الأقصى، وإلى "جامع القـــــرويين" ومعهد "الرصيف" بفاس على وجه الخصوص، وقد ارتبط اسم فاس كثيرا بالثقافة العربية الإسلامية في الجزائر، أين ارتبطت أسماء العديد من علماء ومشايخ العلم والثقافة في الجزائر باسم جامع القرويين، فغص بالعشرات من طلبة العلم، أخذوا منه المعارف الدينية المختلفة، ووجد الطلبة الجزائريون فيه السند القوي في الكفاح، فكان له الفضل الكبير على الحركة الوطنية الجزائرية، حيث أمدها بالشباب المثقف والمتحمس، ليساهموا بها في نشر العربية والإسلام لكفاح الاستعمار. Abstract: The city of Fez in Morocco had established to the culture of resistance since it hold the signature of the treaty of Fez in 30 March 1912, making Morocco into a French protectorate. This city is considered as one of the principal cities attracting Algerians before and after the French colonial of Algeria, for what it's enjoying of geographical location and cultural and civilisational role as the scientific capital of the country. It was the destination of a lot of Algerian migrants coming from different Algerian cities, especially the western ones, as Tlemcen, Mascara, Mustaganem,Oran, and Nedroma. It played an important role in educating and forming Algerian national elites which were engaged in a strong confrontations with the colonialists since 1830 to 1962. In this period the French colonial forces didn't cease of humiliating the Algerian people. After that the movement of free Arab education expanded in Algeria in late thirties of the last century, and has had students who were qualified to began their school and academic studies, the Association of Algerian Muslim Ulama decided to send students missions to Fez in Morocco, and especially to the university of Al Quarouiyine, and Er-Racif Institute in Fez. The name of Fez was too much linked to the Arab and Islamic culture in Algeria, where the names of a lot of scientists and scholars of science and culture in Algeria were linked to the name of the university of Al Quaraouiyine, which was overcrowded with tens of students who learned different religious knowledge. Algerian students found in it a strong support in their struggle, and it has the great merit on the Algerian national movement, it supplied it with cultivated and enthusiastic youths who will contribute to the propagation of Arabic and Islam in the sake of struggling the colonial.
مقال
Keywords: العثات الطلابية، الحركة الاصلاحية، تلمسان، جامع القرويين، فاس